10β,17α-Dihydroxyestra-1,4-dien-3-one: A bioprecursor prodrug preferentially producing 17α-estradiol in the brain for targeted neurotherapy - Prokai-Tatrai, Katalin (ACS Chem Neurosci, 2018)
Uterotrophic effect of 17α-estradiol, the C17 epimer of the main human estrogen 17β-estradiol, was shown to manifest in animal models at doses lower than those necessary for central outcome raising concerns about its potential to treat maladies of the central nervous system. We introduce here 10β,17α-dihydroxyestra-1,4-dien-3-one (α-DHED) that acts as a bioprecursor prodrug producing 17α-estradiol with remarkable selectivity to the brain and, therefore, without appreciable exposure of the periphery to the parent steroid. This distinguishing feature of α-DHED is shown by using an estrogen-responsive mouse model with complementary LC–MS/MS measurement of drug contents in target tissues. Our data warrant further research to fully establish the potential of α–DHED for a safe and efficacious 17α-estradiol-based neurotherapy.